A ANALISIS TERHADAP PENETAPAN DISPENSASI NIKAH MENGGUNAKAN TEORI MASLAHAH : (Penetapan Perkara Nomor : 450/Pdt.P/2020/PA.Jbg) - Ahmad Khotim; Ahmad Insya' Ansori (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2023)
Background. Underage marriage is a marriage that occurs by someone who has not reached the age as intended in Law Number 1 of 1974 concerning Marriage in article 7 paragraph 1 as amended by Law Number 16 of 2019 which states that marriage is only permitted if the parties -The parties are male and female and have reached the age of 19 years. Aim. This research was written to answer the questions outlined in 2 problem formulations, namely: (1) What are the reasons the judge considers when deciding on a request for a marriage dispensation? (2) What is the analysis of the determination of marriage dispensation using maslahah theory in the Jombang Religious Court? Methods. The problem approach method used in this research is a normative juridical approach model, namely an approach that focuses on the norms that apply and originate from juridical provisions. This means both from fiqh books, applicable laws and opinions from legal. Results. The Jombang Regency Religious Court Judge in deciding the Application for Marriage Dispensation uses legal considerations of expediency supported by evidence which according to the judge is quite strong, both written evidence and oral evidence. The judge's policy in giving a decision is in accordance with maslahah because the decision states that if the request for a marriage dispensation is not granted, it will raise fears of adultery or acts prohibited by religion.